Unearthing the dynamics of Indonesia’s geothermal energy development - Yudha, Satya Widya; Tjahjono, Benny; Longhurst, Philip J. (MDPI, 2022)
Indonesia has one of the world’s biggest geothermal energy reserves, accounting for 28.61 Gigawatts of electric energy (GWe). However, as of 2022, the installed geothermal capacity in Indonesia was only around 2.175 GWe, just 7.6% of its estimated potential. Geothermal energy development is required for Indonesia to empower sustainable energy systems and achieve its target of reaching 7.2 GW of geothermal energy by 2025. The geothermal energy sector is viewed as a complex dynamic system, with complicated challenges, including technical, financial, infrastructure, and many other issues. The purpose of this paper is to understand the complex nature of geothermal systems in Indonesia. To that end, this paper examines the geothermal development from a systematic and holistic standpoint, employing the interview technique to enable the conceptualization of the geothermal systems using the system dynamics (SD) approach. The SD model exhibits several underlying and important factors influencing the development of geothermal energy in Indonesia, such as capital investment, the collection of upstream data to reduce risk, infrastructure construction, pricing, incentives, permit procedures, environmental concerns, and public acceptance.
Keywords: geothermal; Indonesia; interview; system dynamics